KONSTRUKSI KEPERCAYAAN KONSUMEN TERHADAP INFLUENCER MARKETING DI ERA KECERDASAN BUATAN: KAJIAN FENOMENOLOGI PADA GENERASI Z INDONESIA - Syabrina Fitriyani; Amelia Amelia (LAP4B, 2026)
This study examines how Generation Z in Indonesia constructs trust toward influencer marketing amid the increasingly massive penetration of artificial intelligence (AI) in the social media ecosystem. The phenomenon of AI-based influencers, synthetic content, and machine learning-powered recommendation algorithms has fundamentally altered the landscape of consumer trust. Using a hermeneutic phenomenological approach with in-depth interview and Focus Group Discussion (FGD) methods, this research involved twenty-three informants aged 18-27 from five major cities in Indonesia who are active users of Instagram, TikTok, and YouTube. Thematic analysis revealed three main themes: (1) skepticism toward the authenticity of AI-generated content, (2) trust reconstruction based on perceived authenticity, and (3) negotiation of consumption identity in AI-saturated digital spaces. The findings indicate that Generation Z's consumer trust is no longer linear and static but dynamic, contextual, and heavily influenced by digital literacy and prior experiences with disappointing content. The theoretical implications of this research enrich the elaboration likelihood model (ELM) and source credibility theory within the context of AI-mediated communication.